2010
DOI: 10.1111/j.1461-9563.2010.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion and excretion of nitrogen by larvae of a cabbage armyworm: the effects of fertilizer application

Abstract: 1 Insect frass has significant impacts on decomposition and soil nitrogen dynamics. Although the frass contains various forms of nitrogen that may differently influence nitrogen dynamics in the decomposition process, how the nitrogen form in the insect frass is influenced by host plant quality remains poorly understood. 2 The present study examined the effects of application of fertilizer on leaf quality of Brassica rapa L. var. perviridis Bailey (Brassicaceae), and on the consumption, frass excretion and fras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…-N. The frass with high NH 4 ? -N clearly resulted from feeding on host plants with a high level of N (Kagata and Ohgushi 2011). Thus, the present study demonstrated that insect frass quality can both positively and negatively influence decomposition and nutrient dynamics in soil.…”
Section: Plant Growth Responses To Frass Additionmentioning
confidence: 52%
See 2 more Smart Citations
“…-N. The frass with high NH 4 ? -N clearly resulted from feeding on host plants with a high level of N (Kagata and Ohgushi 2011). Thus, the present study demonstrated that insect frass quality can both positively and negatively influence decomposition and nutrient dynamics in soil.…”
Section: Plant Growth Responses To Frass Additionmentioning
confidence: 52%
“…perviridis Bailey (Brassicaceae), at various fertilization levels (Kagata and Ohgushi 2011). We showed that the frass quality of M. brassicae larvae was strongly affected by the quality of host plant leaves, and that the larval frass had high levels of total N, nitrate-N (NO 3 --N), and ammonium-N (NH 4 ?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, N enrichment due to N deposition increases N in plants (Fenn et al 1996, Throop and Lerdau 2004). If the plant C:N ratio is less than 14, insect herbivores that feed on those plants may excrete relatively N‐biased frass (Kagata and Ohgushi 2011). In contrast, elevated atmospheric CO 2 level decreases N in plants (Cotrufo et al 1998, Lindroth 2010), and therefore insect herbivores may excrete more C‐biased frass in such an environmental condition (but see Knepp et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Insect frass contains larger amounts of N and labile carbon (C) than leaf litter (Lovett & Ruesink, 1995;Madritch et al, 2007). In addition, insect frass quality is strongly influenced by host leaf quality, such as nitrogen and tannins (Madritch et al, 2007;Kagata & Ohgushi, 2011) which are chemicals known to determine the decomposition efficiency of leaf litter (Enríquez et al, 1993;Kraus et al, 2003). In addition, insect frass quality is strongly influenced by host leaf quality, such as nitrogen and tannins (Madritch et al, 2007;Kagata & Ohgushi, 2011) which are chemicals known to determine the decomposition efficiency of leaf litter (Enríquez et al, 1993;Kraus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%